2018
DOI: 10.2460/ajvr.79.9.980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prostaglandin-mediated and cholinergic-mediated miosis on morphology of the ciliary cleft region in dogs

Abstract: OBJECTIVE To compare morphology of the ciliary cleft (CC) region in dogs after topical administration of latanoprost, pilocarpine, or a combination of latanoprost and pilocarpine. ANIMALS 6 Beagles. PROCEDURES A prospective 4-phase crossover study with washout periods was performed. Latanoprost (phase L), pilocarpine (phase P), pilocarpine followed by latanoprost (phase PL), and latanoprost followed by pilocarpine (phase LP) were administered to the right eye. Artificial tears were administered to the left eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This treatment effect was more obvious in OAG‐affected dogs than in normal dogs and was consistent with previous reports describing the IOP effect of latanoprost and other prostaglandin analogues in these animals 14–16,32–34 . To the best of our knowledge, the underlying mechanism of latanoprost's treatment effects is believed to be a combination of increased uveoscleral and conventional aqueous humor outflow, the latter being facilitated by widening of the canine ciliary cleft via pupil constriction 35,36 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This treatment effect was more obvious in OAG‐affected dogs than in normal dogs and was consistent with previous reports describing the IOP effect of latanoprost and other prostaglandin analogues in these animals 14–16,32–34 . To the best of our knowledge, the underlying mechanism of latanoprost's treatment effects is believed to be a combination of increased uveoscleral and conventional aqueous humor outflow, the latter being facilitated by widening of the canine ciliary cleft via pupil constriction 35,36 …”
Section: Discussionsupporting
confidence: 89%
“…[14][15][16][32][33][34] To the best of our knowledge, the underlying mechanism of latanoprost's treatment effects is believed to be a combination of increased uveoscleral and conventional aqueous humor outflow, the latter being facilitated by widening of the canine ciliary cleft via pupil constriction. 35,36 We observed an obvious circadian treatment effect, especially with the q24h drug administration: Mean IOPs were highest at 8 a.m., 24 h after the last administration, and immediately before the next treatment. Following the eye drop administration at 8 a.m., mean IOPs were lower at the 11:30 a.m. and 3:30 p.m. time points.…”
Section: Discussionmentioning
confidence: 86%
“…Second, uveitis occurs in 90% of non-diabetic dogs immediately after phacoemulsification ( 1 , 32 ). Prostaglandin mediators produced in uveitis can affect CC parameters ( 33 , 34 ). One study reported that the incidence of CCA increased when latanoprost, a prostaglandin mediator, was used alone ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The other ciliary cleft parameters, namely AOD, CCW, and CCA, are associated with its anatomic structure. In other words, if the ciliary cleft collapses, then these parameters also change (Sihota et al, 2005;Hasegawa and Kawata, 2015;Park et al, 2018). Inadequate assessment of structural changes within the ciliary cleft may prevent the early diagnosis of canine primary glaucoma (Hasegawa and Kawata, 2015).…”
Section: Discussionmentioning
confidence: 99%